Manfaat Intervensi Cognitive Behavioural Therapy terhadap Penurunan Kecemasan, Stres, dan Beban Pengasuhan pada Ibu dengan Anak Autism Spectrum Disorder - Agung Tri Yuwono; Yossie Susanti Eka Putri; Herni Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the benefits of Cognitive Behavioral Therapy interventions on parenting stress in mothers with children with Autism Spectrum Disorder (ASD). The method used is a systematic review through article searches adjusted for formulating research questions with the PICO formula in the EBSCOhost, EMBASE, Clinicalkey for Nursing, Proquest, ScienceDirect, and Scopus databases. The study results show that Cognitive Behavioral Therapy can effectively reduce anxiety, stress, and the burden of caring for mothers with children with ASD. In conclusion, interventions through Cognitive Behavioral Therapy have proven effective in reducing anxiety, stress, and the responsibility of caring for mothers with children with ASD. Keywords: Autism Spectrum Disorder, Burden of Parenting, Cognitive Behavior, Anxiety, Stress, Therapy